Un mercato coperto per Roma: Laboratorio di Sintesi finale in Composizione Architettonica e Urbana - Coppola, Nunzia; Criscitiello, Mario; Di Costanzo, Gennaro; Lubrano, Oreste (TeA / Teaching Architecture, 2022)
The book collects the results of the Laboratory of Final Synthesis of the Master Degree course in Architectural Design MAPA at DiARC Department of Architecture, structured around the co-participation of two disciplines, architectural design, taught in the course by Professor Renato Capozzi, and executive design, by Professor Erminia Attaianese. The Laboratory has taken on a call for competition articulated in two phases with the subject of the design of a building with a strong public vocation, with the aim of subjecting the students to a design experimentation based on the simulation of a real participation in a design competition. The roofed market of San Giovanni di Dio in the Monteverde district in Rome, has been the theme of the year for the students, producing ten answers, in which the students have respected both the qualitative and quantitative indications and the number of elaborated required, keeping together the complexity of the architectural project and its executive and constructive aspects. The book is completed by contributions by Carmelo Baglivo, Lorenzo Netti, Valerio Palmieri and Efisio Pitzalis, followed by conclusions by Francesco Costanzo and Federica Visconti